2020
DOI: 10.1080/19490976.2020.1748258
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota profiles of autism spectrum disorder and attention deficit/hyperactivity disorder: A systematic literature review.

Abstract: Accumulating evidence has implicated an involvement of the gut-brain axis in autism spectrum disorder (ASD) and attention-deficit hyperactivity disorder (ADHD), however with highly diverse results. This systematic review aims to describe and evaluate studies investigating the gut microbiota composition in individuals with ASD or ADHD and to evaluate if variations in gut microbiota are associated with these disorders.Twenty-four articles were identified in a systematic literature search of PubMed and Embase up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 105 publications
(312 reference statements)
2
66
1
1
Order By: Relevance
“…We also discussed common factors that contribute to the development of both allergy and neurodevelopmental disorders, and they included maternal depression and anxiety ( 43 46 ), GDM ( 56 , 57 ), maternal allergic status ( 65 , 66 ), environmental factors such as diet and exposure to environmental pollutants ( 77 , 83 ), microbiome dysbiosis ( 90 , 96 ), and sleep disturbances ( 98 , 102 ). However, there is a lack of direct evidence showing that these factors can connect both allergy and neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also discussed common factors that contribute to the development of both allergy and neurodevelopmental disorders, and they included maternal depression and anxiety ( 43 46 ), GDM ( 56 , 57 ), maternal allergic status ( 65 , 66 ), environmental factors such as diet and exposure to environmental pollutants ( 77 , 83 ), microbiome dysbiosis ( 90 , 96 ), and sleep disturbances ( 98 , 102 ). However, there is a lack of direct evidence showing that these factors can connect both allergy and neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…These same bacterial species have also been implicated in neurodevelopmental disorders. A review conducted by Bundgaard-Nielsen et al ( 90 ) on the gut microbiota profiles of ADHD and ASD patients presented convincing evidence on altered gut bacterial composition in ASD individuals as compared with healthy controls, which included increase in Bacteroides and Clostridium as well as the decrease in Bifidobacterium, Streptococcus , and Prevotella in stool microbiota. On the other hand, abundance of Parabacteroides, Prevotella , and Lactobacillus were decreased in ADHD patients.…”
Section: Common Factors Implicated In Both Allergic Diseases and Neurmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there are some efforts to control neurological disorders by applying the gut-brain axis theory, a bidirectional communication between the brain and gastrointestinal tract [ 50 , 51 ]. In cases of ADHD, there is evidence demonstrating that gut microbiota affects brain neurodevelopment [ 52 , 53 , 54 , 55 ]. For instance, Szopinska-Tokov et al suggested that inattentive behavior that appeared in ADHD patients is associated with a specific bacterium [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that the gut microbiota may be an important factor in the development of ASD. The structure and composition of gut microbiota in ASD children differ from those in healthy controls (8)(9)(10). Microbiota transfer therapy (MTT) and dietary modulation of gut microbiota can both alleviate gastrointestinal (GI) dysfunction and behavioral symptoms in children with ASD (11,12).…”
mentioning
confidence: 99%